International Jurisdiction at the Place of Performance of a Contract in Civil (EU) Law: A Jurisdiction Rule Stuck Between the Common Law Perspective and Conflict of Laws Terminology - Banu Şit Köşgeroğlu (Public and Private International Law Bulletin)
The place of performance rule is characterized by its belonging to the European (civil law) legal system. The rule has preserved its existence as a classic rule from Roman law to the present day regarding which local courts will hear the disputes arising from the contracts. Problems related to the interpretation of the place of performance rule, which is also taken as a basis of international jurisdiction, especially in the practice of European Union (EU) law, have emerged since the 1970s; the EU Court of Justice has held that the rule should point to the most closely connected court under the effect of a common law perspective. The closest connection test, which cannot only be seen as a common law effect, also bears traces of the conflict of laws terminology. In this article, it is found that the place of performance rule does not have the function of indicating the most closely connected court, at least in the context of civil law; on the contrary, the rule should be interpreted from the perspective of legal certainty and predictability.